Validation of a French version of the quality of life "Celiac Disease Questionnaire". - Jacques Pouchot; Carole Despujol; Georgia Malamut; Emmanuel Ecosse; Joël Coste; Christophe Cellier (PLoS ONE)
Background and objective Celiac disease (CD) is a common chronic autoimmune disorder. Both the manifestations of the disease and the burden of the compulsory life-long gluten-free diet (GFD) have been shown to be associated with impairment of health-related quality of life. The objectives of this study were to provide a cross-cultural adaptation of the specific quality of life "Celiac Disease Questionnaire" (CDQ) and to analyze its psychometric properties. Materials and methods A cross-cultural French adaptation of the CDQ (F-CDQ) was obtained according to the revised international guidelines. The questionnaire was administered at baseline to 211 patients with biopsy proven CD followed-up in a single tertiary referral centre. The questionnaire was also administered after 7 days and 6 months. Reliability (intraclass correlation coefficients (ICC), Cronbach's alpha and Bland and Altman graphical analysis), validity (factorial structure and Rasch analysis, convergent validity), and responsiveness (effect size) of the F-CDQ were studied. Results The reliability of the F-CDQ was excellent with ICC and Cronbach's alpha coefficients being between 0.79 and 0.94 for the four subscales and the total score. The factorial structure and the Rasch analysis showed that the four dimensions of the original instrument were retained. Correlations with external measures (a generic measure of quality of life, an anxiety and depression instrument, a self-assessed disease severity, and clinical manifestations) were all in the expected direction confirming the validity of the instrument. Responsiveness was studied and effect sizes ≥ 0.20 were demonstrated for most of the subscales for patients who reported improvement or deterioration after 6 months. Conclusion The F-CDQ retains the psychometric properties of the original instrument and should be useful in cross-national surveys and to assess outcome in clinical trials involving patients with CD.